Ab initio simulations of water splitting on hematite. (20th October 2017) - Seriani, Nicola
Abstract: In recent years, hematite has attracted great interest as a photocatalyst for water splitting, but many questions remain unanswered about the mechanisms and the main limiting factors. For this reason, density functional theory has been used to understand the optical, electronic and chemical properties of this material at an atomistic level. Bulk doping can be used to reduce the band gap, and to increase photoabsorption and charge mobility. Charge transport takes place through adiabatic polaron hopping. The stable (0 0 0 1) surface has a stoichiometric termination when exposed to oxygen, it becomes hydroxylated in water, and it has an oxygen-rich termination under illumination in a photoelectrochemical setup. On the oxygen-rich termination, surface states are present that might act as recombination centres for electrons and holes. On the contrary, on the hydroxylated termination surface states appear only on reaction intermediates. The intrinsic surface states disappear in the presence of an overlayer of gallium oxide. The reaction of water oxidation is assumed to proceed by four proton-coupled electron transfers and it is shown to involve a nucleophilic attack with the formation of an OOH group. Calculated overpotentials are in the range of 0.5–0.6 V. Open questions and future research directions are briefly discussed.